2020
DOI: 10.5152/j.aott.2020.03.571
|View full text |Cite
|
Sign up to set email alerts
|

The split transfer of tibialis anterior tendon to peroneus tertius tendon for equinovarus foot in children with cerebral palsy

Abstract: Relationship between the tilt angle of bipolar radial head prostheses and radiological radiocapitellar instability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…n = 68 patient topography unaccounted for). 7 , 8 , 10 All studies included in the review were aligned with treating foot muscle imbalance in spastic CP muscle tone, however the tone abnormality was not graded in severity prior to surgical intervention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…n = 68 patient topography unaccounted for). 7 , 8 , 10 All studies included in the review were aligned with treating foot muscle imbalance in spastic CP muscle tone, however the tone abnormality was not graded in severity prior to surgical intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported use of above-knee casts for at least six weeks with periods of restricted weightbearing, 5 , 12 , 36 with nine reporting the use of below-knee casts and earlier weightbearing. 7 , 8 , 10 , 11 , 14 , 15 , 17 , 29 , 39 Four studies 4 , 5 , 13 , 37 described a combination of above- and below-knee casts. Follow-up times varied widely from one to 16 years, with seven studies 5 , 9 , 10 , 13 , 14 , 29 , 40 reporting outcomes at a mean of five years or more, and six studies over seven years post-surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations